Protean career orientation and organizational commitment: The role of organizational identification - Kyungmin Kim (Global Business & Finance Review (GBFR), 2024)
Purpose: This study investigates the effect of individuals' protean career orientations on their organizational commitment. We expected protean attitudes to be positively related to organizational commitment, based on the perspective that protean career orientation could increase the sense of organizational identification. Design/methodology/approach: We targeted permanent employees from various industries. The survey was conducted through a website, and a total of 572 employees participated in the survey. For analysis, structural equation modeling was used. Findings: The results show that protean career orientation is positively related to organizational commitment, and this relationship is fully mediated by organizational identification. Specifically, affective and normative commitment were positively influenced by protean career orientation, being mediated by organizational identification. Only continuance commitment did not show any relationship with the protean attitude. Research limitations/implications: Despite elucidating the process of mediating, this study limited the variable to organizational identification. The results of this study suggest that more diverse variables (e. g., personality, ideology, values) and approaches (e. g., moderated mediation model) could be investigated in the area of protean career orientation. Originality/value: The results are contrary to previous speculations that protean people are self-centered with insufficient commitment toward the organization. In particular, the positive relationship between protean career orientation and organizational identification is newly suggested, providing a possibility for redefining the core values of protean careers and their potential.
Keywords: 650; Protean career orientation; Organizational commitment; Organizational identification